Characteristics of the international educator and the strategic role of critical incidents. (April 2015) - Savva, Maria
This study explored the characteristics of the international educator through a qualitative analysis of initial decisions to teach abroad. Using interview data from 30 Anglophone educators based across three international schools in China and the Netherlands, the investigation looked beyond surface motives to explore the deeper values which propelled educators overseas. Dominant characteristics included a high value ascribed to travel, as well as a high value ascribed to change and/or risk. How international educators came to ascribe these values was often explained through critical incidents during their formative or young adult years. Analysis of critical incidents suggested that early or repeated exposure to travel, including study abroad experiences, contributed significantly to the development of predispositions towards international employment.